Genetic Structure Analysis in Sugarcane (Saccharumspp.) Using Target Region Amplification Polymorphism (TRAP) Markers Based on Sugar- and Lignin-Related Genes and Potential Application in Core Collection Development - Junior, Carlos Augusto Dias Kanthack; Manechini, Joao Ricardo Vieira [UNESP]; Correa, Ronan Xavier; Pinto, Ana Christina Rossini [UNESP]; Costa, Juliana Borges da; Favero, Thais Monteiro; Pinto, Luciana Rossini (Springer, 2020)
Sugarcane is a main bioenergy crop and is highlighted worldwide in sugar, ethanol, and biomass production. Sugar and lignin contents are important quality traits for traditional and energy cane cultivar development, respectively. In the present study, genetic variability of a broad group of sugarcane basic germplasm accessions encompassing wild relatives and traditional and modern cultivars was assessed using target region amplification polymorphism (TRAP) markers derived from candidate genes involved in sugar and lignin metabolism. In total, 823 polymorphic markers (483 for sugar and 340 for lignin metabolism genes) were amplified; the average polymorphism information content values were highest for sugarcane wild relatives followed by traditional cultivars and modern cultivars. Genetic variability of the 96 genotypes captured by TRAP candidate genes for sugar and lignin metabolism was structured into two and three subpopulations, respectively. Based on the membership proportion (Q), modern cultivars inherited variability for genes involved in sugar metabolism from bothS. officinarumandS. spontaneum.The genetic differentiation index based on sugar and lignin metabolism genes suggests moderate genetic differentiation among wild relatives, traditional cultivars, and modern cultivars. A core collection was established for sugar and lignin TRAP markers. Values for average genetic distance for the core collection based on sugar (0.761) and lignin (0.804) TRAP-derived markers were higher than those observed for all accessions, indicating that the core collections retained the most divergent accessions.
Keywords: Breeding; Diversity; Fibre; Molecular marker; Sugar